The Influence Of Product And Promotion On Purchase Decisions (A Study On Saga Cake & Cookies Sintang) - Erga Ofiananda Pratama; Yasir Hudzaifah; Joko Susilo (UNIVED Press, 2025)
This study aims to evaluate the influence of product and promotional techniques on consumer purchasing decisions at Saga Cake & Cookies in Sintang Regency. The research employed a quantitative methodology via a survey approach, with data gathered via survey forms administered to 100 participants. The employed data analysis procedures encompass validity assessments, reliability evaluations, classical assumption tests (normality, linearity, multicollinearity), multiple linear regression, and hypothesis testing. The data indicates that neither product nor promotion significantly influences purchasing decisions, whether considered together or individually. This is demonstrated by a significant value of 0.05 and a coefficient of determination (R²) of 0.006, indicating that merely 0.6% of the purchasing decision variable might be clarified by the goods and promotion. Consequently, variables beyond product and promotion are likely to exert a more substantial influence on consumer purchasing decisions at Saga Cake & Cookies.